Bosnia and Herzegovina - From Aid Dependency to Fiscal Self-Reliance : A Public Expenditure and Institutional Review - World Bank (Washington, DC, 2013)
Over the medium term, Bosnia and Herzegovina will go through a critical phase of fiscal adjustment and deeper economic reforms as it moves to orient its economy to the market and to increased integration with the rest of Europe. A key finding of this report is that the present size and scope of public spending cannot be sustained. This report is aimed at helping the authorities identify the priority fiscal policy and institutional issues and reform options on which the medium-term adjustment agenda will need to focus. The report is divided into five chapters. Chapter 1 describes the evolving governance framework and assesses its macroeconomic and fiscal stance. Chapter 2 examines government spending. Chapter 3 looks at present intergovernmental fiscal relations. Chapter 4 assesses public spending in the social sectors. Finally, chapter 5 analyzes public expenditure management and financial accountability systems.